Analysis of Problem-Based Learning Implementation in Improving Students’ Critical Thinking Skills in Biology Education: Analisis Penerapan Model Problem Based Learning dalam Meningkatkan Keterampilan Berpikir Kritis Siswa pada Pembelajaran Biologi - Hesa Dwinata Pandia; Annisa Pristy; Maureen Efriyanti Sitinjak; Yanda Febry Gracea Br.Tarigan; Rizal Mukra; Widya Arwita (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in improving students' critical thinking skills in biology learning. This research uses a qualitative descriptive approach. Data collection was conducted through observation, interviews, and literature study techniques. The subjects in this study were biology teachers and students participating in learning using this model. The results showed that the application of the PBL model made a positive contribution to the development of students' critical thinking skills. Based on observation results, the percentage of students' critical thinking skills substantially increased from 40% before the application of the PBL model to 80% after the learning intervention was carried out. Qualitative data from teacher interviews also confirmed that the use of the PBL model encouraged students to be more confident in discussing, expressing opinions, and asking critical questions. Overall, the PBL model is effective in developing critical thinking skills through a student-centered learning process.